2020
DOI: 10.1007/s10006-020-00851-w
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing periodontitis or medication-related osteonecrosis of the jaw (MRONJ) in a patient receiving Bemcentinib—a case report

Abstract: Bemcentinib is a newly developed AXL inhibitor that is currently under investigation in phase II trails for the treatment of acute myeloblastic leukemia (AML). Clinical and radiographic findings in this case were very similar to cases of MRONJ in patients receiving Sunitinib or other anti-angiogenetic substances, assuming that Bemcentinib may cause similar oral side effects. We present a male 81-year-old patient with a manifestation of alveolar bone necrosis at the central upper incisors following a 2-month re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…To assess the efficacy of pharmacologic inhibition of the AXL pathway on endometrial fibrosis, a selective small molecule inhibitor against AXL, Bemcentinib, which has been used to perform clinical trials for treating cancers (Yule et al , 2018 ; Bumm et al , 2020 ), was given by oral administration (80 mg/kg, p.o., MedChemExpress; Holland et al , 2010 ; Lijnen et al , 2011 ) in an IUA mouse model. We performed two kinds of time points for the treatment: one begun 7 days later after the first curettage and one begun at the same day of the first curettage (Fig 7A and Appendix Fig S8 A).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the efficacy of pharmacologic inhibition of the AXL pathway on endometrial fibrosis, a selective small molecule inhibitor against AXL, Bemcentinib, which has been used to perform clinical trials for treating cancers (Yule et al , 2018 ; Bumm et al , 2020 ), was given by oral administration (80 mg/kg, p.o., MedChemExpress; Holland et al , 2010 ; Lijnen et al , 2011 ) in an IUA mouse model. We performed two kinds of time points for the treatment: one begun 7 days later after the first curettage and one begun at the same day of the first curettage (Fig 7A and Appendix Fig S8 A).…”
Section: Resultsmentioning
confidence: 99%
“…13 Interestingly, MRONJ has been observed in patients with acute myelodysplastic leukemia treated with bemcentinib via an antiangiogenic mechanism and interference with the host immunological profile. 14 Owosho et al 15 have also reported cases of MRONJ, after ipilimumab, a monoclonal antibody administered in patients with malignant melanoma, and acts by inhibiting the immune system via CTLA-4 activation. Lastly, MRONJ has also been described after therapy surface of T-cells in a variety of cancers such as lung cancer.…”
Section: Why Does This Paper Matter?mentioning
confidence: 99%
“…MRONJ has also been associated with herceptin and pertuzumab, monoclonal antibodies administered in Her2‐positive breast cancer patients 13 . Interestingly, MRONJ has been observed in patients with acute myelodysplastic leukemia treated with bemcentinib via an anti‐angiogenic mechanism and interference with the host immunological profile 14 . Owosho et al 15 have also reported cases of MRONJ, after ipilimumab, a monoclonal antibody administered in patients with malignant melanoma, and acts by inhibiting the immune system via CTLA‐4 activation.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the efficacy of pharmacologic inhibition of the AXL pathway on endometrial fibrosis, a selective small molecule inhibitor against AXL, Bemcentinib, which has been used to perform clinical trials for treating cancers (Yule, et al,2018;Bumm, et al,2020), was given by oral administration (80 mg/kg, p.o., MedChemExpress) (Holland, et al,2010;Lijnen, et al,2011) in an IUA mouse model. We performed two…”
Section: Inhibition Of Axl Ameliorates Endometrial Fibrosis and Resto...mentioning
confidence: 99%